How to Live on Mars With a Proper Circadian Clock? - Luo, Rujia; Huang, Yutao; Ma, Huan; Guo, Jinhu (Frontiers in Astronomy and Space Sciences, 2022)
Intrinsic circadian clocks generate circadian rhythms of physiology and behavior, which provide the capabilities to adapt to cycling environmental cues that result from the self-rotation of the Earth. Circadian misalignment leads to deleterious impacts on adaptation and health in different organisms. The environmental cues on the interplanetary journey to and on Mars dramatically differ from those on Earth. These differences impose numerous adaptive challenges, including challenges for humans’ circadian clock. Thus, adaptation of circadian rhythms to the Martian environment is a prerequisite for future landing and dwelling on Mars. Here, we review the progress of studies associated with the influence of the Martian environment on circadian rhythms and propose directions for further study and potential strategies to improve the adaptation of the circadian clock for future Mars missions.